Media Edukasi Game Puzzle dalam Meningkatkan Kemampuan Berhitung pada Anak Usia Dini - M, Padma Mike Putri (LPPM UNIKA Santo Thomas Medan, 2023)
Artificial Intelligence has a broad scope, such as learning media. Puzzles are included in the branch of AI science. Learning using puzzles has enormous benefits because this learning attracts interest and increases the cognitive thinking power of children who are new to numbers. This game is very fun for children so that this learning can be done until it's finished. Puzzle games can be in various forms of numbers, pictures, colors and others. The puzzle city consists of 0rdo 3x3 so the arrangement of numbers 1-8 and 1 is left blank for the shift position. In this study using serial numbers 1-8 which are specifically intended for young children who are new to seeing and knowing numbers. The way to play this game is to arrange a series of numbers from 1-8 in the correct order. The purpose of this research is to help improve mindsets, increase understanding of numbers. The algorithm used in this study is the Best First Search Algorithm, the working process of this algorithm is in the form of determining the root node to the queue. The advantage of this method is finding the best solution. The downside is that it requires a large amount of memory because the process is very long. The completion process requires 8 iterations because the puzzle position is in a position that has no truth value. After the process, the final result of the puzzle position is B=8, so the search is stopped.